2019
DOI: 10.3892/ol.2019.11162
|View full text |Cite
|
Sign up to set email alerts
|

Serum coiled‑coil domain containing 25 protein as a potential screening/diagnostic biomarker for cholangiocarcinoma

Abstract: Coiled-coil domain containing 25 (CCDC25) was previously reported to be upregulated in cholangiocarcinoma (CCA) tissues compared with adjacent normal tissues. The present study investigated whether serum CCDC25 level may be used as a potential marker for the diagnosis of CCA. Bioinformatics tools were used to reveal that CCDC25 is secreted into plasma/serum via a non-conventional pathway, which secretes proteins independently from the endoplasmic reticulum/golgi complex, but is yet to be fully elucidated. Subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…To the best of our knowledge, coiled-coil domain-containing protein 25 (CCDC25) has been described in relation to BMS in this study for the first time. This protein is highly conserved among mammals and its expression is almost ubiquitous in human tissues; however, its function is still unclear [ 31 ]. This protein has been proposed recently as a serum biomarker of chronic cholangitis and cholangiocarcinoma [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, coiled-coil domain-containing protein 25 (CCDC25) has been described in relation to BMS in this study for the first time. This protein is highly conserved among mammals and its expression is almost ubiquitous in human tissues; however, its function is still unclear [ 31 ]. This protein has been proposed recently as a serum biomarker of chronic cholangitis and cholangiocarcinoma [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This protein is highly conserved among mammals and its expression is almost ubiquitous in human tissues; however, its function is still unclear [ 31 ]. This protein has been proposed recently as a serum biomarker of chronic cholangitis and cholangiocarcinoma [ 31 ]. However, there is no data about CCDC25 and saliva or BMS and, therefore, further studies should be performed to clarify its possible relation.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study (6), we reported that CCDC25 was intracellularly overexpressed in CCA cells, especially after bile acid treatment, and was overexpressed in CCA tissues in comparison to the corresponding adjacent noncancerous tissues. We also reported that the serum CCDC25 level of CCA patients was higher than that of healthy controls, suggesting that CCDC25 can be a diagnostic biomarker for CCA (7). In this study, therefore, we examined CCDC25 levels in the patients' sera from highly prevalence cancers in Thailand including CRC, BC, HCC, and CCA, to evaluate their diagnostic value.…”
mentioning
confidence: 97%
“…For instance, apurinic/apyrimidinic endodeoxyribonuclease 1 (APEX-1) was a secreted protein which identified as a potential serum marker for diagnosis and prognosis of CCA ( 16 ). Moreover, other members of our group identified coiled-coil domain containing 25 (CCDC25), apoptosis-inducing factor, mitochondrion-associated 3 (AIFM3) and cytokine-induced apoptosis inhibitor 1 (CIAPIN1) as potential secreted protein biomarkers in CCA ( 17 19 ). In this study, we performed liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis of CCA patients' sera who were pathologically diagnosed with both vascular invasion and lymph node metastasis with ≤ 1 year survival time and >1 year survival time for searching a potential prognostic biomarker of CCA.…”
Section: Introductionmentioning
confidence: 98%